Application of Internet-Based Language Learning in Teaching English Classes at Faculty of Languages at the University of Benghazi in Post-Pandemic Coronavirus - Omar, Dr.Youssif Zaghwani (مجلة كلية الاداب, 2022)
This paper handles the application of Internet-Based Language Learning (IBLL) in teaching English classes at Faculty of Languages at the University of Benghazi, Libya. Teaching English at Libyan universities in general is based on teacher-centered lecturing, in which students sit passively take whatever provided to them from their instructors. This traditional strategy of teaching had encountered challenges due to closure of the university because of the pandemic of Coronavirus by the beginning of 2020, which required shifting to virtual online teaching. The researcher of this paper has conducted this paper to investigate about this new experience of learning and teaching at the Faculty of Languages at the University of Benghazi. The researcher uses qualitative research method, in which he uses literature review as secondary resources and interviewing a sample of students from Faculty of Languages at the University of Benghazi as primary resources. Findings of the study reveal that students and teacher encounter challenging in applying IBLL, the biggest challenges are represented in weakness of the Internet and black out of the power. The researcher presents recommendations based on the findings obtained.